La destrucción de los embriones congelados (1997)
This article deals whit a piece of news about the death of 3,300 embryos and its relation to Great Britain's legislation in August, 1990 an the controversy this event ethically not only form a social perspective but also from parent's point of view, emphasizing the individual value of each frozen embryo.